The effect of mono- and disaccharides influence on structural-mechanical properties of gels - Dorohovich, Antonella; Dorohovich, Victoriya; Kambulova, Yuliia (My University, 2016)
The effect of glucose, fructose, sucrose and lactulose on structural and mechanical properties and thixotropic gel pectin in apple puree. A comparative analysis of participation mono- and disaccharides in the formation of pectin gel. Determined loss prebiotic lactulose storage gels. Calculated rational relationship apple sauce and sugar to form functional confectionery recipes appointment.
Keywords: pectin gels; glucose; fructose; thixotropy; functional products; пектинові гелі; глюкоза; фруктоза; тиксотропія; функціональні продукти; кафедра технології хлібопекарських і кондитерських виробів; пектиновые гели; тиксотропия; функциональные продукты